2010
DOI: 10.1111/j.1439-0531.2009.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Melatonin against Hydrogen Peroxide‐Induced Oxidative Stress on Boar Sperm Characteristics and Subsequent In Vitro Embryo Development

Abstract: Melatonin, the major secretory product of the pineal gland, scavenges a variety of reactive oxygen and nitrogen species in vivo and in vitro, indicating that melatonin is a potent function as an antioxidant. The objective of this study was to investigate the effect of melatonin in the presence or absence of hydrogen peroxide (H(2)O(2)) on sperm characteristics (motility, viability, survival rate, membrane integrity, lipid peroxidation (LPO) and mitochondria activity) and also to examine the developmental rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 46 publications
(53 reference statements)
9
82
0
1
Order By: Relevance
“…Therefore, the melatonin secreted by the testes can have the same function as that found in pre-ovulatory follicular fluid, which is to protect the spermatozoa from oxidative damage that could impair male fertility (Agarwal et al, 2008). Incubation of ejaculated spermatozoa with melatonin has resulted in decreased apoptotic-related changes in many species (Casao et al, 2010b;Dom ınguez-Rebolledo et al, 2010;Jang et al, 2010;Balao da Silva et al, 2011), including human (Du Plessis et al, 2010;Espino et al, 2011). Moreover, melatonin can not only act upon fully mature spermatozoa but also during spermatogenesis in the seminiferous tubules (Guneli et al, 2008;Ozen et al, 2008) and upon epidydimal spermatozoa (Huang et al, 2009;Sarabia et al, 2009), reducing oxidative damage, apoptosis, and DNA breakages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the melatonin secreted by the testes can have the same function as that found in pre-ovulatory follicular fluid, which is to protect the spermatozoa from oxidative damage that could impair male fertility (Agarwal et al, 2008). Incubation of ejaculated spermatozoa with melatonin has resulted in decreased apoptotic-related changes in many species (Casao et al, 2010b;Dom ınguez-Rebolledo et al, 2010;Jang et al, 2010;Balao da Silva et al, 2011), including human (Du Plessis et al, 2010;Espino et al, 2011). Moreover, melatonin can not only act upon fully mature spermatozoa but also during spermatogenesis in the seminiferous tubules (Guneli et al, 2008;Ozen et al, 2008) and upon epidydimal spermatozoa (Huang et al, 2009;Sarabia et al, 2009), reducing oxidative damage, apoptosis, and DNA breakages.…”
Section: Discussionmentioning
confidence: 99%
“…MLT has a key role in the regulation of the circadian wake-sleep cycle, immune enhancement, and also adjusting of seasonal reproduction (Reiter 1973). Moreover, it can stimulate the activity of antioxidant enzymes such as SOD and GSH-Px (Jang et al 2010). Interestingly, human seminal fluid contains melatonin and spermatozoa reportedly possess membrane receptor of melatonin (Ortiz et al 2011).…”
Section: The Addition Of Melatonin (Mlt)mentioning
confidence: 98%
“…Trolox at the low millimolar range (0.1-1 mM) had a protective effect on thawed red deer spermatozoa by preventing rising of intracellular ROS and lipid peroxidation as well as by preventing DNA damage (Domínguez-Rebolledo et al 2009, 2010Martínez-Pastor et al 2008, 2009. Anel-López et al (2012) reported that Trolax is not a suitable extender supplement for the cryopreservation of epididymal deer spermatozoa, at least at the low millimolar range, since they found a decrease in motility and mitochondrial activity.…”
Section: The Supplementation Of Antioxidants In the Freezing Extendersmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, melatonin implantation into male animals significantly elevated serum testosterone levels which subsequently increased sperm number, motility and the fertilization rate (Casao et al, 2010). Furthermore, eggs fertilized by melatonin-treated sperms have significantly higher developmental rates to the blastocyst stage (Jang et al, 2010). Considering these findings, it is now thought that melatonin is not always antigonadotropic.…”
Section: Discussionmentioning
confidence: 99%